A Study of Psychological Impact of Recent Natural Disaster ‘Nisarg’ and Socio-Economic Factors Associated with It on People in Coastal Maharashtra - Jage, Poorva; Sangamnerkar, Sayee; Raje, Swati Sanjeev (National Journal of Community Medicine, 2020)
Background: Natural disasters are known to have prolonged psychological impact on the people who face them. In India where 60% of population depends on agriculture, such natural calamities cause great psychological stress along with economic loss. Identifying the factors associated with psychological morbidities will help in planning preventive measures to mitigate the burden of disease in such disaster-prone areas. Objectives: To assess prevalence of psychological stress, depression and anxiety among the individuals who faced ‘Nisarga’ cyclone and the socio-economic factors associated with it. Methods: A cross sectional study was done among the people of costal Maharashtra 2 months after severe cyclone Nisarga had hit the area. Data was collected using a structured questionnaire from a stratified random sample of people from various occupations. Data was analysed using SPSS 26 software. Result: It was observed that 75% of the study samples were extreme cases of anxiety, almost 60% had extremely severe depression and nearly half of the population had extremely severe stress Age severity of problem and financial loss were significantly associated with severity of depression anxiety and stress. In addition, Severity of Depression was associated with Gender, and severity of stress was significantly associated with type of family. Conclusion: Quick assessment of economic damage and rehabilitation will help in reducing severity of psychological depression, anxiety and stress among people facing natural disaster.